Method for green and efficient resource utilization of titanium gypsum
Through sodium carbonate modification and hydrochloric acid leaching treatment of titanium gypsum, combined with alkaline precipitation and liquid-liquid reaction, the problems of low resource utilization rate of titanium gypsum and the impact of iron impurities are solved, efficient iron removal and calcium recovery are achieved, and energy consumption and cost are reduced.
Patent Information
- Application Number
- CN202411936492.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Titanium gypsum has low resource utilization and high iron impurities content, which affects its mechanical properties and widespread application. The existing iron removal methods consume high energy and cost, making it difficult to achieve large-scale continuous production.
By modifying titanium gypsum by sodium carbonate, calcium sulfate is converted into calcium carbonate that is easily eroded by acid, and hydrochloric acid leaching treatment is used to achieve high iron removal and calcium leaching rate. Subsequently, pH was adjusted by alkaline solution, chemical precipitation was performed to obtain high-grade Fe2O3, and CaSO4 and NaCl were synthesized by liquid-liquid reaction.
The efficient removal and recovery of iron and calcium in titanium gypsum was achieved, with the iron removal rate reaching more than 97%, the Ca leaching rate reaching more than 99%, and the Fe2O3 grade reached more than 82%, reducing energy consumption and production costs and promoting comprehensive resource utilization.
Smart Images

Figure CN119747370A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of comprehensive resource utilization of titanium gypsum, and specifically to a method for realizing green and efficient resource utilization of titanium gypsum. Background Art
[0002] Titanium gypsum (TG) is an industrial gypsum produced by neutralizing a large amount of acidic wastewater with lime or carbide slag during the sulfuric acid process of producing titanium dioxide. Its main component is calcium sulfate (CaSO4·2H2O). Since titanium gypsum contains a large amount of amorphous hydrogen Fe2O3, it is usually red in color and is also called red gypsum. One ton of titanium dioxide can produce 6 to 10 tons of titanium gypsum. According to statistics, China's titanium gypsum production will reach 30 million tons in 2023, but the comprehensive utilization rate is very low, only 10%. The main problems facing titanium gypsum at present are: (1) large emissions, low utilization rate, and difficulty in resource utilization; (2) many metal impurities and high iron impurity content, which seriously affect the mechanical properties of titanium gypsum; (3) low mechanical strength, high water content, and high viscosity, which limit its wide application in building materials and other fields. Because of this, the main uses of titanium gypsum are limited to cement retarders, composite cementitious materials, wall materials, etc., with a narrow scope of application and low product added value. The main industrial method of treating titanium gypsum is landfill or stockpiling, which not only occupies a large amount of land but also causes serious pollution to the surrounding soil, water and atmosphere, ultimately affecting human health. Therefore, there is an urgent need to find environmentally friendly and efficient methods to utilize titanium gypsum.
[0003] Titanium gypsum has a complex composition and a high impurity content. Among them, the iron impurity content is the highest. The presence of impurities has an adverse effect on the utilization of titanium gypsum, such as affecting the whiteness, moisture absorption, and anti-frost of the product. Therefore, it is necessary to remove impurities from titanium gypsum. At present, the methods for extracting iron are mainly divided into dry iron removal and wet iron removal. Dry iron removal includes reduction-magnetic separation and chlorination. The dry method has high operating costs and high energy consumption. Wet iron removal includes extraction, reduction bleaching, acid leaching, flotation, and liquid phase reduction-magnetic separation. The most commonly used method is acid leaching. The acid leaching method uses H+ substitution to generate soluble iron compounds with a high iron removal rate.
[0004] At present, there are some literatures on the comprehensive utilization of titanium gypsum resources, such as:
[0005] 1. Patent application CN103086624B discloses a method for preparing α-hemihydrate gypsum from titanium gypsum. The method is to control the system to maintain an acidic condition of pH 1.8-2.5 during the reaction of titanium dioxide waste acid and calcium carbonate (or soda lime), so that the iron element in the titanium dioxide waste acid exists in the form of ferric sulfate, and then filter and dry to obtain iron-removing titanium gypsum, and mix the iron-removing titanium gypsum and salt solution at a solid-liquid mass ratio of 1:4-6 to obtain a slurry, and then add a crystal conversion agent, adjust the pH of the slurry to 3-6, and recrystallize at 92-102°C to obtain α-hemihydrate gypsum slurry, and then mix the α-hemihydrate gypsum slurry with hot water and stir to separate the solid and liquid, wash the separated solid phase with hot water, fix with ethanol, filter, and dry to obtain an α-hemihydrate gypsum product. It can be seen that the patent does not make comprehensive use of the iron element. The Fe2O3 content in titanium gypsum is about 10%-18%, and the iron content is relatively high. However, the patent does not involve the effective recovery of the iron element in titanium gypsum, resulting in waste of resources and environmental pollution.
[0006] 2. Patent application CN118978353A discloses a method for preparing high value-added gypsum products by deep iron removal of high-iron gypsum. The method first removes part of the iron in titanium gypsum by acid leaching treatment, and then deeply removes iron by dissolving process regulated by gypsum phase. At the same time, the existence form of iron in solution is regulated to prevent it from entering the gypsum lattice during recrystallization, and the morphology and particle size of the recrystallized product are regulated by adding a crystal form regulator, and the adsorption of iron on the surface of the gypsum product is weakened. Finally, the iron and gypsum products are separated efficiently by releasing iron and weakening the adsorption effect of iron, and high-purity and high-strength α-hemihydrate gypsum is formed at the same time. The process flow of this method is complicated, the operation is cumbersome, and the production cost is increased. First, sulfuric acid treatment is used to remove part of the iron in titanium gypsum, and then the iron impurities in the titanium gypsum inclusions are removed by phase reconstruction to achieve deep removal. The two-step method removes iron, and the initial iron removal rate is only 60%, resulting in low overall efficiency and difficulty in realizing large-scale continuous production. Moreover, the method mainly focuses on the removal of iron rather than recovery, and fails to make full use of the precious resource of iron in titanium gypsum, resulting in waste of resources.
[0007] 3. Patent application CN110342561B discloses a method for efficient iron removal from gypsum, a byproduct of titanium dioxide produced by the sulfuric acid process. The method includes weighing and proportioning, mixing and stirring, primary extraction, primary magnetic separation, secondary extraction, secondary magnetic separation, precipitation and filtration, etc. to achieve adsorption and separation of iron ions in titanium gypsum. The method uses secondary extraction and secondary magnetic separation, which requires multiple steps, increases equipment investment, operation complexity and production costs, and multi-stage processing leads to low overall process efficiency. The method mainly focuses on the removal of iron rather than recycling, and fails to make full use of the precious resource of iron in titanium gypsum, resulting in waste of resources and not in line with the concept of circular economy.
[0008] 4. Patent application CN105502464B discloses a process for separating and removing iron from titanium gypsum. The method first pre-treats the titanium gypsum and grinds it into a powder with a particle size of 800 mesh, then uses hydrogen to reduce the titanium gypsum at high temperature to convert the iron in the titanium gypsum into magnetic Fe3O4, and then uses magnetic separation equipment to separate and remove it. This method requires high-temperature reduction of titanium gypsum and special magnetic separation equipment, resulting in extremely high energy consumption and strict equipment requirements, and the iron removal rate is also low.
[0009] 5. Patent application CN116986832B discloses an integrated method for removing impurities from titanium gypsum by microwave pressurization and preparing high-strength gypsum. The method adds titanium gypsum to a sulfuric acid solution and uses a microwave reactor to pressurize the hydrothermal reaction to remove impurities from the titanium gypsum. The titanium gypsum after impurity removal is mixed with deionized water, maleic acid or sodium citrate is added to adjust the crystal form, and high-strength gypsum with high morphology is synthesized by microwave heating technology. This method requires microwave pressurization. Microwave heating under high-pressure conditions places higher requirements on the safety of the equipment. Any leakage may lead to dangerous accidents. In addition, microwave radiation may also pose a threat to human health, requiring strict safety measures and protective facilities, which increases operating costs.
[0010] Therefore, it is very important to develop an energy-saving and environmentally friendly process for comprehensive utilization of iron in titanium gypsum. Summary of the invention
[0011] In order to solve the above technical problems existing in the prior art, the present application provides a green and efficient method for realizing resource utilization of titanium gypsum, which is as follows:
[0012] A green and efficient method for realizing resource utilization of titanium gypsum comprises the following steps:
[0013] (1) ball-milling and sieving the iron-containing titanium gypsum, and then adding it to a modifier aqueous solution for pretreatment, continuously keeping warm and fully stirring in a water bath, and then separating the solid and liquid to obtain modified slag and Na2SO4 solution, wherein the separated modified slag is modified titanium gypsum; the modifier is sodium carbonate;
[0014] (2) adding the modified titanium gypsum of step (1) into an inorganic acid solution, mixing to form a suspension slurry, performing acid leaching, and then performing solid-liquid separation to obtain an acid leaching solution containing calcium and iron and silicon-titanium leaching residue;
[0015] (3) adjusting the pH of the calcium- and iron-containing acid leaching solution in step (2) with an alkaline solution, causing chemical precipitation, aging, and then performing solid-liquid separation to obtain a calcium-containing filtrate and an iron-enriched precipitate;
[0016] (4) roasting the iron-enriched precipitate obtained in step (3) to obtain high-grade Fe2O3;
[0017] (5) The Na2SO4 solution of step (1) and the calcium-containing filtrate of step (3) are subjected to liquid-liquid reaction to obtain CaSO4 and NaCl.
[0018] Furthermore, in the step (1), the wet modification conditions are as follows: the amount of modifier added is 38% to 42%, the modification temperature is 25 to 30°C, the modification time is 58 to 62 min, the liquid-solid ratio is 12:1 ml / g, and the stirring rate is controlled at 296 to 305 rpm.
[0019] Furthermore, in the step (1), the aqueous solution of the modifier is prepared by dissolving the modifier in distilled water, completely dissolving the modifier and heating the water to a desired temperature before adding titanium gypsum for modification.
[0020] Furthermore, in the step (1), ball milling and screening is to use a ball mill to ball mill the raw material titanium gypsum, and then pass it through a 200-mesh standard sieve.
[0021] Furthermore, in the step (1), the filter residue is washed with distilled water until it becomes neutral, and then placed in a forced air drying oven for drying at a temperature of 100° C. for 24 hours.
[0022] Furthermore, in the step (2), the modified titanium gypsum is ground and passed through a 200-mesh standard sieve, and then added to a hydrochloric acid solution for acid leaching reaction.
[0023] Furthermore, in step (2), the inorganic acid is hydrochloric acid, and the acid leaching conditions are: hydrochloric acid mass fraction is 14% to 16%, temperature is 68 to 72° C., time is 59 to 65 min, liquid-to-solid ratio is 10:1 ml / g, and rotation speed is 296 to 310 rpm.
[0024] Furthermore, in step (2), during the acid leaching, the culture dish needs to be covered to form a closed environment to prevent the hydrochloric acid from volatilizing.
[0025] Furthermore, in step (3), the alkaline solution is aqueous ammonia.
[0026] Furthermore, in step (3), the pH value is adjusted to 2.9-4.0 using a 10% ammonia solution.
[0027] Furthermore, in step (3), the aging experimental conditions are: temperature of 68-72° C. and time of 25-30 min.
[0028] Furthermore, in step (4), the calcination is to place the iron-enriched precipitate in a tubular furnace at 500° C. and calcine for 1 hour.
[0029] Furthermore, in the step (5), the liquid-liquid reaction is to mix the calcium-containing filtrate with the Na2SO4 solution in a volume ratio of 1:0.5-3 to obtain a slurry.
[0030] The present invention firstly converts the main component of the raw material, calcium sulfate, into calcium carbonate that is easily corroded by acid by modifying titanium gypsum with sodium carbonate, thereby obtaining modified titanium gypsum and Na2SO4 solution, and then acid-leaching the modified titanium gypsum with hydrochloric acid, thereby leaching iron oxide and calcium into the solution together, thereby achieving a high iron removal rate and calcium leaching rate. The acid leaching solution is mainly composed of chlorides of calcium and iron, and the pH of the acid leaching solution is adjusted by alkaline substances to precipitate iron, and solid-liquid separation is performed to obtain iron-enriched precipitation and calcium-containing filtrate, and then the iron-enriched precipitation is roasted to obtain high-grade Fe2O3. The modified Na2SO4 solution and the calcium-containing filtrate are reacted in liquid-liquid reaction to obtain CaSO4 and NaCl products.
[0031] Compared with the prior art, the technical effects created by this application are embodied in:
[0032] 1. The present invention uses sodium carbonate to modify titanium gypsum. During the entire modification process, by controlling the amount of modifier added and the liquid-solid ratio of the modified slurry, the long strip and plate-shaped calcium sulfate in the titanium gypsum can be fully converted into flaky calcium carbonate that is easily corroded by acid, so that the leaching efficiency of the modified titanium gypsum is effectively improved during the acid leaching process, and the conversion rate of calcium sulfate reaches more than 96%. The entire modification process is carried out at room temperature, the modification conditions are mild, the energy consumption is low, and the cost of comprehensive utilization of titanium gypsum is reduced.
[0033] 2. The present invention reasonably controls the process parameters of hydrochloric acid leaching of modified titanium gypsum, so that calcium carbonate and iron oxides in the modified titanium gypsum are effectively leached by hydrochloric acid, and converted into soluble calcium and iron chlorides. The iron removal rate reaches more than 97%, and the Ca leaching rate reaches more than 99%, achieving high iron removal rate and calcium leaching rate, fast reaction speed, and can complete the leaching process in a short time, thereby improving production efficiency.
[0034] 3. The present invention reasonably controls the pH range of the acid leaching solution and the process parameters of the Na2SO4 solution and the calcium-containing filtrate, so that the iron and calcium in the titanium gypsum are recycled, and the Fe2O3 grade reaches more than 82%. The use of wet iron removal avoids operation at a high temperature, reduces energy consumption during the experiment, and has great energy-saving advantages.
[0035] 4. The advantage of the method of the present invention is that sodium carbonate is used to modify titanium gypsum to obtain calcium carbonate that is easily corroded by acid, and then hydrochloric acid is used to acid-leach the modified titanium gypsum to achieve a high iron removal rate and Ca leaching rate. The iron and calcium in the acid leaching solution can be directly separated by regulating the pH by alkaline substances, and high-grade Fe2O3 is obtained after roasting, and then Na2SO4 solution and calcium-containing filtrate are synthesized into CaSO4 and NaCl. This process is simple and easy to operate, has high iron removal efficiency, fast reaction speed, low production cost, and promotes comprehensive resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a flowchart of this application. DETAILED DESCRIPTION
[0037] The technical solution of the present application is further limited below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.
[0038] The present application example uses a titanium gypsum from Sichuan as a raw material, and analyzes its chemical composition, and the mass fractions of its components are shown in the following Table 1:
[0039] Table 1 Chemical composition and content of titanium gypsum (wt%)
[0040] Element CaO <![CDATA[SO3]]> C <![CDATA[Fe2O3]]> <![CDATA[SiO2]]> MgO <![CDATA[Al2O3]]> <![CDATA[TiO2]]> other content 37.34 34.19 10.53 9.70 2.75 1.84 1.32 1.27 1.06
[0041] Table 2 Experimental Examples 1 to 7 Experimental Proportions and Dosages
[0042] Titanium gypsum / g Sodium carbonate / g Hydrochloric acid mass fraction / % Acid leaching temperature / ℃ Example 1 100 40 5 30 Example 2 100 40 10 30 Example 3 100 40 15 30 Example 4 100 40 20 30 Example 5 100 40 15 50 Example 6 100 40 15 70 Example 7 100 40 15 90
[0043] Example 1
[0044] A green and efficient method for realizing resource utilization of titanium gypsum comprises the following steps:
[0045] (1) After ball-milling and sieving titanium gypsum, place it in a forced air drying oven and dry it at 100°C for more than 12 hours. Then, dissolve the modifier in distilled water, completely dissolve it, heat it to the required temperature, and then add the titanium gypsum for modification. After continuous heat preservation and sufficient stirring for a period of time in a water bath, separate the solid and liquid to obtain modified titanium gypsum and Na2SO4 solution. The wet modification conditions are: the amount of modifier added is 40%, the modification temperature is 25°C, the modification time is 60min, the liquid-solid ratio is 12:1ml / g, and the stirring rate is controlled at 300rpm. The modifier is sodium carbonate. The titanium gypsum, modifier and water are mixed according to the following weight ratio: 100g titanium gypsum, 40g modifier, and 1200ml distilled water. The ball milling and sieving is to use a ball mill to ball mill the raw titanium gypsum and then pass it through a 200-mesh standard sieve.
[0046] (2) The modified titanium gypsum of step (1) was placed in a 100° C. forced air drying oven and dried to constant weight, wherein the iron content was 14.08% and the conversion rate of calcium sulfate was 96.21%.
[0047] (3) The modified titanium gypsum of step (1) is ground, sieved, dried, and acid-leached, and then solid-liquid separation is performed to remove iron, so as to obtain an acid leaching solution containing calcium and iron and a silicon-titanium leaching residue. The acid leaching solution is then subjected to an alkaline solution to adjust the pH, chemical precipitation, and aging, and then solid-liquid separation is performed to obtain a calcium-containing filtrate and an iron-enriched precipitate; the modified titanium gypsum is ground and sieved through a 200-mesh standard sieve, and then placed in a forced air drying oven for drying at a temperature of ≥100°C for 1 to 4 hours; the inorganic acid is hydrochloric acid, and the acid leaching conditions are: a hydrochloric acid mass fraction of 5%, a temperature of 30°C, a time of 60 minutes, a liquid-solid ratio of 10:1 ml / g, and a rotation speed of 300 rpm; the alkaline solution is used to adjust the pH to 3.5 using a 10% ammonia solution; and the aging time is 30 minutes.
[0048] (4) The iron-enriched precipitate of step (3) was calcined in a tubular furnace at 500° C. for 1 h, and its Fe2O3 content was 52.75%, the iron removal rate was 46.02%, and the Ca leaching rate was 92.78%.
[0049] (5) 200 ml of the Na2SO4 solution of step (1) and 200 ml of the calcium-containing filtrate of step (3) were mixed to form a slurry, and a liquid-liquid reaction was performed at room temperature to obtain CaSO4 and NaCl.
[0050] Example 2
[0051] A green and efficient method for realizing resource utilization of titanium gypsum comprises the following steps:
[0052] (1) After ball-milling and sieving titanium gypsum, place it in a forced air drying oven and dry it at 100°C for more than 12 hours. Then, dissolve the modifier in distilled water, completely dissolve it, heat it to the required temperature, and then add the titanium gypsum for modification. After continuous heat preservation and sufficient stirring for a period of time in a water bath, separate the solid and liquid to obtain modified titanium gypsum and Na2SO4 solution. The wet modification conditions are: the amount of modifier added is 40%, the modification temperature is 27°C, the modification time is 61min, the liquid-solid ratio is 12:1ml / g, and the stirring rate is controlled at 302rpm. The modifier is sodium carbonate. The titanium gypsum, modifier and water are mixed according to the following weight ratio: 100g titanium gypsum, 40g modifier, and 1200ml distilled water. The ball milling and sieving is to use a ball mill to ball mill the raw titanium gypsum and then pass it through a 200-mesh standard sieve.
[0053] (2) The modified titanium gypsum of step (1) was placed in a 100° C. forced air drying oven and dried to constant weight, wherein the iron content was 14.08% and the conversion rate of calcium sulfate was 96.21%.
[0054] (3) The modified titanium gypsum of step (1) is ground, sieved, dried, and acid-leached, and then solid-liquid separation is performed to remove iron, thereby obtaining an iron-containing acid leaching solution and a silicon-titanium leaching residue. The acid leaching solution is then subjected to an alkaline solution to adjust the pH value, chemical precipitation, and aging, and then solid-liquid separation is performed to obtain a calcium-containing filtrate and an iron-enriched product; the modified titanium gypsum is ground and sieved through a 200-mesh standard sieve, and then placed in a forced air drying oven for drying at a temperature of ≥100°C for 1 to 4 hours; the inorganic acid is hydrochloric acid, and the acid leaching conditions are: a hydrochloric acid mass fraction of 10%, a temperature of 30°C, a time of 60 minutes, a liquid-solid ratio of 10:1 ml / g, and a rotation speed of 302 rpm; the alkaline solution is used to adjust the pH value to 3.0 using a 10% ammonia solution; and the aging time is 30 minutes.
[0055] (4) The iron-enriched precipitate of step (3) was calcined in a tubular furnace at 500° C. for 1 h, and its Fe2O3 content was 75.05%, the iron removal rate was 91.78%, and the Ca leaching rate was 99.16%.
[0056] (5) 200 ml of the Na2SO4 solution of step (1) and 100 ml of the calcium-containing filtrate of step (3) were mixed to form a slurry, and a liquid-liquid reaction was performed at room temperature to obtain CaSO4 and NaCl.
[0057] Example 3
[0058] A green and efficient method for realizing resource utilization of titanium gypsum comprises the following steps:
[0059] (1) After ball milling and sieving titanium gypsum, place it in a blast drying oven and dry it at 100°C for more than 12 hours. Then, dissolve the modifier in distilled water, completely dissolve it, heat it to the required temperature, and then add the titanium gypsum for modification. After continuous heat preservation and sufficient stirring for a period of time in a water bath, separate the solid and liquid to obtain modified titanium gypsum and Na2SO4 solution. The wet modification conditions are: the amount of modifier added is 40%, the temperature is 27°C, the time is 61min, the liquid-solid ratio is 12:1ml / g, and the stirring rate is controlled at 305rpm. The modifier is sodium carbonate. The titanium gypsum, modifier and water are mixed according to the following weight ratio: 100g titanium gypsum, 40g modifier, and 1200ml distilled water. The ball milling and sieving is to use a ball mill to ball mill the raw titanium gypsum and then pass it through a 200-mesh standard sieve.
[0060] (2) The modified titanium gypsum of step (1) was placed in a 100° C. forced air drying oven and dried to constant weight, wherein the iron content was 14.08% and the conversion rate of calcium sulfate was 96.21%.
[0061] (3) The modified titanium gypsum of step (1) is ground, sieved, dried, and acid-leached, and then solid-liquid separation is performed to remove iron, thereby obtaining an iron-containing acid leaching solution and a silicon-titanium leaching residue. The acid leaching solution is then subjected to an alkaline solution to adjust the pH value, chemical precipitation, and aging, and then solid-liquid separation is performed to obtain a calcium-containing filtrate and an iron-enriched product; the modified titanium gypsum is ground and sieved through a 200-mesh standard sieve, and then placed in a forced air drying oven for drying at a temperature of ≥100°C for 1 to 4 hours; the inorganic acid is hydrochloric acid, and the acid leaching conditions are: a hydrochloric acid mass fraction of 15%, a temperature of 30°C, a time of 60 minutes, a liquid-solid ratio of 10:1 ml / g, and a rotation speed of 305 rpm; the alkaline solution is used to adjust the pH value to 3.1 using a 10% ammonia solution; and the aging time is 30 minutes.
[0062] (4) The iron-enriched precipitate of step (3) was calcined in a tubular furnace at 500° C. for 1 h, and its Fe2O3 content was 78.25%, the iron removal rate was 95.98%, and the Ca leaching rate was 99.34%.
[0063] (5) 200 ml of the Na2SO4 solution of step (1) and 400 ml of the calcium-containing filtrate of step (3) were mixed to form a slurry, and a liquid-liquid reaction was performed at room temperature to obtain CaSO4 and NaCl.
[0064] Example 4
[0065] A green and efficient method for realizing resource utilization of titanium gypsum comprises the following steps:
[0066] (1) After ball-milling and sieving titanium gypsum, place it in a blast drying oven and dry it at 100°C for more than 12 hours. Then, dissolve the modifier in distilled water, completely dissolve it, heat it to the required temperature, and then add the titanium gypsum for modification. After continuous heat preservation and sufficient stirring for a period of time in a water bath, separate the solid and liquid to obtain modified titanium gypsum and Na2SO4 solution. The wet modification conditions are: the amount of modifier added is 40%, the temperature is 25°C, the time is 60min, the liquid-solid ratio is 12:1ml / g, and the stirring rate is controlled at 301rpm. The modifier is sodium carbonate. The titanium gypsum, modifier and water are mixed according to the following weight ratio: 100g titanium gypsum, 40g modifier, and 1200ml distilled water. The ball milling and sieving is to use a ball mill to ball mill the raw titanium gypsum and then pass it through a 200-mesh standard sieve.
[0067] (2) The modified titanium gypsum of step (1) was placed in a 100° C. forced air drying oven and dried to constant weight, wherein the iron content was 14.08% and the conversion rate of calcium sulfate was 96.21%.
[0068] (3) The modified titanium gypsum of step (1) is ground, sieved, dried, and acid-leached, and then solid-liquid separation is performed to remove iron, thereby obtaining an iron-containing acid leaching solution and a silicon-titanium leaching residue. The acid leaching solution is then subjected to an alkaline solution to adjust the pH value, chemical precipitation, and aging, and then solid-liquid separation is performed to obtain a calcium-containing filtrate and an iron-enriched product; the modified titanium gypsum is ground and sieved through a 200-mesh standard sieve, and then placed in a forced air drying oven for drying at a temperature of ≥100°C for 1 to 4 hours; the inorganic acid is hydrochloric acid, and the acid leaching conditions are: a hydrochloric acid mass fraction of 20%, a temperature of 30°C, a time of 60 minutes, a liquid-solid ratio of 10:1 ml / g, and a rotation speed of 300 rpm; the alkaline solution is used to adjust the pH value to 3.3 using a 10% ammonia solution; and the aging time is 30 minutes.
[0069] (4) The iron-enriched precipitate of step (3) was calcined in a tubular furnace at 500° C. for 1 h, and its Fe2O3 content was 79.55%, the iron removal rate was 96.20%, and the Ca leaching rate was 99.38%.
[0070] (5) 200 ml of the Na2SO4 solution of step (1) and 600 ml of the calcium-containing filtrate of step (3) were mixed to form a slurry, and a liquid-liquid reaction was performed at room temperature to obtain CaSO4 and NaCl.
[0071] Example 5
[0072] The difference from Example 1 is that the experimental conditions for hydrochloric acid leaching modified titanium gypsum are: hydrochloric acid mass fraction of 15%, temperature of 50°C, time of 60min, liquid-solid ratio of 10:1ml / g, rotation speed of 300rpm, and other conditions remain unchanged. Its Fe2O3 content is 80.10%, iron removal rate is 96.78%, and Ca leaching rate is 99.65%.
[0073] Example 6
[0074] The difference from Example 1 is that the experimental conditions for hydrochloric acid leaching modified titanium gypsum are: hydrochloric acid mass fraction of 15%, temperature of 70°C, time of 60min, liquid-solid ratio of 10:1ml / g, rotation speed of 300rpm, and other conditions remain unchanged. Its Fe2O3 content is 82.32%, iron removal rate is 97.57%, and Ca leaching rate is 99.70%.
[0075] Example 7
[0076] The difference from Example 1 is that the experimental conditions for hydrochloric acid leaching modified titanium gypsum are: hydrochloric acid mass fraction of 15%, temperature of 90°C, time of 60min, liquid-solid ratio of 10:1ml / g, rotation speed of 300rpm, and other conditions remain unchanged. Its Fe2O3 content is 82.50%, iron removal rate is 97.94%, and Ca leaching rate is 99.70%.
[0077] In summary, the present application first modifies titanium gypsum with sodium carbonate, converts the main component of the raw material, calcium sulfate, into calcium carbonate that is easily corroded by acid, so that the conversion rate of calcium sulfate in titanium gypsum reaches 96.21%, and then uses hydrochloric acid to acid-leach the modified titanium gypsum, with an iron removal rate of 97.57% and a Ca leaching rate of 99.70%. A high iron removal rate and calcium leaching rate are achieved. After chemical precipitation of the acid leaching solution, the Fe2O3 grade reaches 82.50%. The Na2SO4 solution modified with sodium carbonate in the first step and the calcium-containing filtrate of the hydrochloric acid acid leaching in the second step are liquid-liquid reacted to synthesize Ca2SO4 and NaCl products. This method can achieve efficient removal and recovery of iron and calcium in titanium gypsum, with fast reaction speed and low production cost, avoiding operation at higher temperatures in the existing pyrometallurgical process, reducing energy consumption during the experiment, having great energy-saving advantages, and promoting comprehensive resource utilization.
[0078] Finally, it should be pointed out that the above embodiments are only representative examples of the present application. Obviously, the technical solution of the present application is not limited to the above embodiments, and there may be many variations. All variations that can be directly derived or associated with the contents disclosed in the present application by a person of ordinary skill in the art should be considered as the protection scope of the present application.
Claims
1. A green and efficient method for realizing resource utilization of titanium gypsum, characterized in that: The following steps are involved: (1) ball-milling and sieving the iron-containing titanium gypsum, and then adding it to a modifier aqueous solution for pretreatment, continuously keeping warm and fully stirring in a water bath, and then separating the solid and liquid to obtain modified slag and Na2SO4 solution, wherein the separated modified slag is modified titanium gypsum; the modifier is sodium carbonate; (2) adding the modified titanium gypsum of step (1) into an inorganic acid solution, mixing to form a suspension slurry, performing acid leaching, and then performing solid-liquid separation to obtain an acid leaching solution containing calcium and iron and silicon-titanium leaching residue; (3) adjusting the pH of the calcium- and iron-containing acid leaching solution in step (2) with an alkaline solution, causing chemical precipitation, aging, and then performing solid-liquid separation to obtain a calcium-containing filtrate and an iron-enriched precipitate; (4) roasting the iron-enriched precipitate obtained in step (3) to obtain high-grade Fe2O3; (5) The Na2SO4 solution of step (1) and the calcium-containing filtrate of step (3) are subjected to liquid-liquid reaction to obtain CaSO4 and NaCl.
2. The green and efficient method for realizing resource utilization of titanium gypsum according to claim 1 is characterized in that: The step (1), wherein the wet modification conditions are: the wet modification conditions are: the amount of modifier added is 38% to 42%, the modification temperature is 25 to 30°C, the modification time is 58 to 62 minutes, the liquid-solid ratio is 12:1 ml / g, and the stirring rate is controlled to be 296 to 305 rpm.
3. The green and efficient method for realizing resource utilization of titanium gypsum according to claim 1 is characterized in that: In the step (1), the aqueous solution of the modifier is prepared by dissolving the modifier in distilled water, completely dissolving the modifier and heating the water to a desired temperature before adding titanium gypsum for modification.
4. The green and efficient method for realizing resource utilization of titanium gypsum according to claim 1 is characterized in that: In the step (1), ball milling and screening is to use a ball mill to ball mill the raw material titanium gypsum, and then pass it through a 200-mesh standard sieve.
5. The green and efficient method for realizing resource utilization of titanium gypsum according to claim 1 is characterized in that: In the step (1), the filter residue is washed with distilled water until it becomes neutral, and then placed in a forced air drying oven for drying at a temperature of 100° C. for 24 hours.
6. The green and efficient method for realizing resource utilization of titanium gypsum according to claim 1 is characterized in that: In the step (2), the modified titanium gypsum is ground and passed through a 200-mesh standard sieve, and then added to a hydrochloric acid solution for acid leaching reaction.
7. The green and efficient method for realizing resource utilization of titanium gypsum according to claim 1 is characterized in that: In the step (2), the inorganic acid is hydrochloric acid, and the acid leaching conditions are: hydrochloric acid mass fraction is 14% to 16%, temperature is 68 to 72° C., time is 59 to 65 min, liquid-to-solid ratio is 10:1 ml / g, and rotation speed is 296 to 310 rpm.
8. The green and efficient method for realizing resource utilization of titanium gypsum according to claim 7 is characterized in that: In the step (2), during the acid leaching, the culture dish needs to be covered to form a closed environment to prevent the hydrochloric acid from volatilizing.
9. The green and efficient method for resource utilization of titanium gypsum according to claim 1, characterized in that: In the step (3), the aging experimental conditions are: temperature of 68-72° C. and time of 25-30 min.
10. The green and efficient method for resource utilization of titanium gypsum according to claim 1, characterized in that: In the step (5), the liquid-liquid reaction is to mix the calcium-containing filtrate with the Na2SO4 solution in a volume ratio of 1:0.5-3 to obtain a slurry.
Citation Information
Patent Citations
Method for processing phosphogypsum
CN101508447A
Method for preparing alpha-semi-hydrated gypsum from titanium gypsum
CN103086624A
Method for preparing high-quality calcium sulfate whiskers and calcium oxide by using industrial byproduct gypsum
CN110965124A
Gypsum tailing treatment method for solid lithium ore neutralization process
CN114988484A
Method for preparing high-purity gypsum and byproduct sodium acetate trihydrate by taking phosphogypsum as raw material
CN116534888A
Cited By
Method for purifying titanium gypsum and recycling leachate
CN120589774A